Matrix metalloproteinases and their inhibitors in human vitreous. - De La Paz, MA; Itoh, Y; Toth, C; Nagase, H (1998)
PURPOSE: To conduct zymographic analysis to study the matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinases (TIMPs) in vitreous samples of patients undergoing pars plana vitrectomy as part of the treatment of vitreoretinal disease. METHODS: Forty-two vitreous samples were collected at the time of pars plana vitrectomy. Diagnoses included severe (exudative) age-related macular degeneration (AMD) (12), macular hole (10), presumed ocular histoplasmosis syndrome (6), proliferative diabetic retinopathy (PDR) (5), epiretinal membrane (4), vitreomacular traction syndrome (2), macroaneurysm with subretinal hemorrhage (1), central retinal vein occlusion with vitreous hemorrhage (1), and proliferative vitreoretinopathy (1). Gelatin zymography, reverse gelatin-zymography, carboxymethylated transferrin zymography, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis were performed on the liquid vitreous samples to assess for MMP and TIMP activity. RESULTS: Progelatinase A occurred in all vitrectomy samples. In addition, a band consistent with TIMP-2 occurred in all samples on reverse zymography. An inhibitor of MMP of a lower molecular weight than TIMP-1 was found in all the samples. A serine proteinase with a broad band around 180 kDa was found in 2 of the 11 AMD vitreous samples. A 75-kDa metalloproteinase was found in several AMD samples, but it was much more abundant in the PDR samples. CONCLUSIONS: Metalloproteinases and their endogenous inhibitors are present in human vitreous and may be involved in the pathogenesis of PDR and other vitreoretinal diseases.